Effect of the axial gap on the energy consumption of a single-blade wastewater pump. (May 2021) - Caruso, Federico; Meskell, Craig
The effect of the axial gap on the energy consumption of a single-blade wastewater pump (Sulzer XFP PE-2 150E CB1.1) is assessed using unsteady Reynolds-averaged Navier–Stokes simulations with ANSYS Fluent. The numerical model was compared to experimental data with a nominal design configuration (i.e. gap size) to provide confidence in the modeling approach. The global performance of the pump was evaluated in terms of pressure-discharge, torque, and efficiency for a range of volumetric flow rates (110 m 3 ċh −1 to 254 m 3 ċh −1 ) and gap sizes (0.3 mm to 1.15 mm). While it is found that the power consumption at a given flow rate is reduced with increased gap, this is at the expense of a drop in outlet pressure, and hence the efficiency of the pump drops significantly. At the largest volumetric flow rate considered (254 m 3 ċh −1 ), the sensitivity of the efficiency to the gap size is −13.5%ċmm −1 and the sensitivity of the reduction in mechanical power consumption to gap size is 0.58 kWċmm −1 . These results emphasize the importance of active maintenance during the lifetime of a wastewater pump to avoid a reduction in the energy performance caused by increased gap size.